Exposure to improved nutrition from conception to age 2 years and adult cardiometabolic disease risk: a modelling study. Issue 8 (August 2018) - Ford, Nicole D; Behrman, Jere R; Hoddinott, John F; Maluccio, John A; Martorell, Reynaldo; Ramirez-Zea, Manuel; Stein, Aryeh D
Summary: Background: Low-income and middle-income countries with populations that are chronically undernourished in early life are undergoing a nutrition transition and are experiencing an epidemic of cardiometabolic disease. These dual burdens are thought to be causally related; therefore, the extent to which improvements in early-life nutrition can offset adult-onset disease is important. The aim of this study was to examine whether improvement of protein-energy nutrition from conception to age 2 years can attenuate the risk of cardiometabolic disease. Methods: We followed up a cohort of 2392 individuals born between Jan 1, 1962, and Feb 28, 1977, in four villages in Guatemala who had participated in a cluster-randomised protein-energy nutritional supplementation (Atole) trial. Of 1661 participants available for follow-up from Feb 26, 2015, to April 29, 2017, we studied 683 women and 456 men. We assessed cardiometabolic disease risk at ages 37–54 years using anthropometry, fasting and post-challenge glucose, fasting lipid concentrations, and blood pressure. We used generalised linear and logistic regression modelling to estimate the effect of Atole from conception to age 2 years (the first 1000 days) on cardiometabolic disease risk. Findings: Exposure to Atole from conception to age 2 years was associated with increased fatness (body-mass index [BMI, 1·30 kg/m 2, 95% CI 0·14 to 2·46], body fat [1·47%, −0·01 to 2·94], and obesity [odds ratio 1·99, 1·16 to 3·41]), and reduced odds of diabetes (odds ratio 0·47, 0·22 to 0·99). We found stratum heterogeneity by sex in pooled models for BMI (1·06 kg/m 2, 95% CI −0·60 to 2·71, for women vs 1·56, 0·07 to 3·05, for men), waist circumference (1·54 cm, −2·31 to 5·40, for women vs 4·38, 0·61 to 8·15, for men), waist-to-height ratio (0·01, −0·02 to 0·04, for women vs 0·02, 0·00 to 0·04, for men), and body fat (0·75%, −1·07 to 2·57, for women vs 2·61, 0·18 to 5·04, for men). p values for interaction of sex and exposure to Atole from conception to age 2 years were 0·06, 0·07, 0·04, and 0·09, respectively. Interpretation: Improved protein-energy nutrition from conception to the 2nd birthday reduced the odds of diabetes at ages 37–54 years; however, this protein-energy supplementation also increased the risk of obesity and several obesity-related conditions. Our findings suggest a mixed ability of protein-energy nutritional supplementation in early life to prevent adult cardiometabolic disease incidence in the context of high childhood stunting and high adult overweight and obesity. Funding: National Institutes of Health.